Estudo de um reator solar híbrido para cura acelerada do concreto em água morna - Gonçalves, Denilson Pereira (2012)
The Portland cement concrete material is the most consumed after the water worldwide due to their versatility molding, strength and durability as a structural material. The curing is the procedure that aims to keep the concrete saturated with water in their early ages and it is essential to ensure the reactions of cement hydration, promoting its consolidation as artificial rock. Curing accomplished through controlled procedures is essential to promote or measure the performance potential of concrete, both resistance and durability. The curing of concrete is therefore an important variable to be controlled in the works, in assays for quality control of the material in manufacturing processes of prefabricateds or also in research. Moreover, the normal period and ideal curing concrete that lasts 28 days is in excess in all cases cited, so it is usual the prediction of the strength by early ages or shorter periods by accelerated curing of the concrete. In this work, the main objective was to design and test a hybrid solar reactor to promote accelerated curing of concrete in warm water, a modified method of the Type A ASTM C 684:1999, seeking a future evolution to a Brazilian test method that can be used in quality control of concrete. The major design challenges were address control and distribution of the temperature inside the reactor and to test the time reduction of curing Portland cement pastes from 28 days in water at 23°C to 7 days in water at warm 35°C. The reactor was assembled in the laboratory and consists of a solar water heater attached to a sealed tank, and that alone should keep the warm water at the temperature indicated. Should make maximum use of solar energy, ie, with greater use of renewable and clean energy. Account is also supported by an electric heater and a generator to supply power on cloudy days or in a possible power outage by the local distributor or maintenance of the electrical system. The water/cement ratio of the cement pastes studied ranged between 0.25 and 0.35 kg/kg and the development of hydration was monitored both by thermogravimetric analysis and by tests of compression strength. The sample tests pastes cured in the reactor at 35°C, initially followed the curing range of ASTM Method A (0 to 24h) and they also were tested in the other three options for adapting the accelerated test (24 to 48 h, 24 h to 72h and 24 h to 168 h), because the period 0-24 h is only feasible in a laboratory situation. The sample test pastes underwent cure (23°C) were tested at 7 and 28 days. It was concluded that there were changes in hydration during the three tested accelerated periods, but even within 24 h to 168 h accelerated curing the pastes not achieved the strength of normal curing after 28 days.